A novel drug conjugate, NEO212, targeting proneural and mesenchymal subtypes of patient-derived glioma cancer stem cells. Issue 2 (28th February 2016) - Jhaveri, Niyati; Agasse, Fabienne; Armstrong, Don; Peng, Lilei; Commins, Deborah; Wang, Weijun; Rosenstein-Sisson, Rachel; Vaikari, Vijaya Pooja; Santiago, Shayane V.; Santos, Tiago; Chen, Ligang; Schönthal, Axel H.; et al.
Highlights: Four populations of glioma stem cells (GSCs) were isolated from four different patient-derived specimens. GSCs were genetically and phenotypically characterized as proneural and mesenchymal. NEO212, temozolomide–perillyl alcohol conjugate, induced cytotoxicity in GSCs. At equimolar doses NEO212 was at least tenfold more cytotoxic to GSC than temozolomide. NEO212 delayed GSC-derived tumor growth and increased survival in vivo . Abstract: Glioblastoma multiforme (GBM), a highly malignant brain tumor, accounts for half of all gliomas. Despite surgery, radiation and chemotherapy, the median survival is between 12 and 15 months. The poor prognosis is due to tumor recurrence attributed to chemoresistant glioma cancer stem cells (GSCs). Here we examined the effects of a novel compound NEO212, which is composed of two covalently conjugated anti-cancer compounds – temozolomide (TMZ) and perillyl alcohol (POH), on GSCs expressing either the proneural or mesenchymal gene signatures. These GSCs were obtained from patient-derived tumor tissue. Our findings demonstrate that NEO212 is 10 fold more cytotoxic to GSCs than TMZ (standard-of-care). Furthermore, NEO212 is effective against both proneural and clinically aggressive mesenchymal GSC subtypes. The mechanism of NEO212 mediated-cytotoxicity is through double-strand DNA breaks and apoptosis. In vivo studies show that NEO212 significantly delays tumor growth of both proneural and mesenchymal tumor stem cell populations. Patient-derived GSCs and tumors derived from these cells are highly reflective of the heterogeneity in human GBM. The efficacy of NEO212 against both GSC subtypes indicates that NEO212 has great clinical potential to effectively target GBM.